Passive Immunity Transfer in Water Buffaloes (Bubalus bubalis) - Souza, Damazio Campos de [UNESP]; Silva, Daniela Gomes da [UNESP]; Fonseca, Lana Cristine Coelho [UNESP]; Castro Fiori, Leticia de [UNESP]; Monteiro, Bruno Moura; Bernardes, Otavio; Viana, Rinaldo Batista; Fagliari, Jose Jurandir [UNESP] (Frontiers Media Sa, 2020)
This study aimed to evaluate passive immunity transfer in healthy buffalo calves. Colostrum samples from heifers (without previous calving) and primiparous and pluriparous dams and blood samples from their offspring were obtained at calving, before colostrum intake, and at 24, 48, and 72 h after calving for determination of serum activities of gammaglutamyltransferase and alkaline phosphatase and serum concentrations of total protein (TP), immunoglobulin A (IgA) and IgG, and lactoferrin. The results were analyzed as repeated measures, and differences were considered statistically significant atP <= 0.05. Considering that the buffalo calves were born hypogammaglobulinemic (4.23 +/- 0.33 mg/ml) and, at 24 h, the mean serum concentration of IgG was 34.5 +/- 1.48 mg/ml, passive immunity transfer was successful. Moreover, colostrum IgG concentrations at 0 h were correlated with serum IgG concentrations at 24 h in buffalo calves. Additionally, TP concentrations were highly correlated with IgG in both colostrum at calving and blood in calves at 24 h. TP is recommended as a reliable indirect parameter to evaluate both colostrum quality and passive immunity transfer in buffalo calves.
Keywords: calf; colostrum; murrah; IgG; neonate; newborn